Reaktualisasi Hukum Islam di Indonesia (Analisis Terhadap Teori Hudūd Muhammad Syahrur) - Hendri Hermawan Adinugraha (Universitas Muhammadiyah Purwokerto (UMP), 2018)
The purpose of this study is to describe contemporary Islamic legal thought of Muhammad Syahrur with the limit theory (hudūd) in re-actualizing Islamic law and then correlated with the development of Islamic law in Indonesia. This research method used a literature approach that was still relevant to the reform of Islamic law in Indonesia based on Syahrur’s perspective. The result of literature study already showed that the re-actualizing of Islamic law with Syahrur’s linguistic approach in studying the Qur’an has been highly dependent on the socio-cultural context. Syahrur considered the need for reinterpretation of the Qur’anic texts in synchronizing the texts with the reality of society whenever and wherever. The limit theory of Syahrur has been an interpretation’s result of language and mathematical integration analysis in understanding the verses of the law, through the theory of this limit, Syahrur tried to apply the muhkamat texts into the reality of life with its limitations. The laws in the Qur’an according to him were elastic that be able to drawn and adapted into the context of place and age. Contextualization of Syahrur’s limit theory as the basis for legal reform in Indonesia can be proved in the matter of inheritance, the concept of determining zakat, the constraints of aurat, polygamy, and Islamic criminal law.